Investigating the efficacy of uncrosslinked porcine collagen coated vascular grafts for neointima formation and endothelialization - Yang, Chao; Su, Chao; Zou, Jie; Zhong, Binru; Wang, Lin; Chen, Bailang; Li, Jianmo; Wei, Minxin (Frontiers in Bioengineering and Biotechnology, 2024)
This study evaluates the efficacy of uncrosslinked porcine collagen coated vascular grafts (UPCCVG) in facilitating neointima formation and endothelialization. Prior to coating, the uncrosslinked porcine collagen underwent comprehensive characterization employing SDS-PAGE, image analysis, circular dichroism and immunogenicity. The PET substrate of the vascular graft was coated with collagen solution utilizing the dip-coating method. Water permeability, blood leakage resistance, radial compliance, hemolysis, cytotoxicity and cell proliferation of UPCCVG in vitro were studied. Subsequent in vivo evaluation involved the implantation of UPCCVG as a substitute for the porcine abdominal aorta. Digital subtraction angiography (DSA) was employed to evaluate UPCCVG patency post-implantation, while histology, immunohistochemistry, and scanning electron microscopy were utilized to assess neointima formation and endothelialization. The in vivo thrombosis of UPCCVG was analyzed simultaneously to further characterize its blood compatibility. The uncrosslinked collagen demonstrated high purity, maintaining its triple helix structure and molecular weight akin to the type I bovine collagen standard substrate, indicative of preserved biological activity and low immunogenicity. UPCCVG exhibited water permeability, blood leakage resistance, radial compliance and blood compatibility comparable to commercial grafts. DSA revealed satisfactory patency of UPCCVG without evidence of stenosis or swelling at the 3-week post-implantation mark. Histological analysis illustrated well-developed neointima with appropriate thickness and controlled proliferation. Immunohistochemistry confirmed the presence of endothelial cells (VWF positive) and smooth muscle cells (α-SMA positive) within the neointima, indicating successful endothelialization. Moreover, the morphology of the neointima surface closely resembled that of the natural artery tunica intima, oriented along the direction of blood flow. UPCCVG, composed of uncrosslinked porcine collagen, demonstrates promising potential in fostering neointima formation and endothelialization while mitigating intimal hyperplasia. This biocompatible uncrosslinked porcine collagen merits further investigation for its clinical applications in vascular reconstruction.